Freezing goat embryos at different developmental stages and quality using ethylene glycol and a slow cooling rate - Fonseca, J. F.; Batista, R. I. T. P.; Souza-Fabjan, J. M. G.; Oliveira, M. E. F. [UNESP]; Brandao, F. Z.; Viana, J. H. M. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2018)
The efficiency of an alternative freezing protocol for goat embryos of different morphology and quality was tested. Fifty-eight embryos on Day 6-7 stage were transferred as fresh or after freeze-thawing (n=29/group). For freezing, embryos were placed into 1.5M ethylene-glycol solution for 10min. During this time, they were loaded in the central part of 0.25mL straw, separated by air bubble from columns containing PBS/BSA 0.4% plus 20% BFS. Straws were then frozen using a freezing machine from 20 degrees C to -6 degrees C at a cooling rate of 3 degrees C/min, stabilization for 15min (seeding after 5min), from -6 C to -32 degrees C at 0.6 C/min, and plunged into liquid nitrogen. Frozen embryos were thawed for 30s at 37 degrees C in a water bath. Embryos subjected to fresh transfer were maintained in holding medium (37 degrees C). Fresh and frozen-thawed embryos were transferred at day 7 post-estrus to 30 recipients. Kidding and kid born rates were similar (P> 0.05), respectively, for recipients receiving fresh (66.7% or 10/15; 55.2% or 16/29) or frozen-thawed (60% or 9/15; 51.7% or 15/29) embryos. The cryopreservation of goat embryos using slow-freezing protocol and 1.5MEG resulted in similar efficiency rates of fresh embryos.
Keywords: embryo survival; embryo transfer; goat; slow freezing